Effects of dietary xylanase-treated rice husk on performance characteristics of West African Dwarf goats Capra hircus - Kolade, Isiaka Oyeniyi; Yousuf, Mahmud Baba; Salako, Abiola Yemi; Ajijolakewu, Kamoldeen Abiodun; Abdulkareem, Tajjudeen Zakari; Sesan, Lawal Wasiu (Aceh Journal of Animal Science, 2024)
The effect of feeding value ofAspergillus tubingensisxylanase-treated rice husk supplemented in the dietary treatment to improve nutrient intake and digestibility, nitrogen retention and body weight gain in WAD goats was investigated. Twenty (20) West African Dwarf (WAD) goats of four to six (4-6) months old with a live weight of 6.5 - 6.6 kg were randomly allotted to four dietary treatments and a control with two replicates comprising two animals in each treatment group in a completely randomized design (CRD). Crude xylanase produced was used for enzymatic degradation of rice husk which enhanced fibre digestion, increases nutritional values and improves performance of WAD goats. The rice husk was initially subjected to physical pre-treatment through milling to increase the surface area. Pre-treated rice husk was treated by spraying the xylanase onto the rice husk at 100g/0.2mL. Xylanase-treated rice husk (XTRH) was used with other ingredients in formulating WAD goat diets at treatment levels of 0 (control), 10%, 20%, 30% and 40% (XTRH). The goat was fed on feeding trial for 56 days. Growth performance, nutrient digestibility and rumen fermentation parameters were evaluated. Crude protein intake and nutrient digestibility was significantly highest (p 0.05) for goats fed diet 4 with 30% inclusion level of xylanase-treated rice husk than for those fed at 10%, 20%, 40% or the control. Differences in feed nutrient intake and digestibility caused gradual improvement (p 0.05) in body weight gain from 16.07 (g/head/day) in the un-supplemented group to 42.88 (g/head/day) in goats fed at 30% (XTRH) inclusion level. Results showed that performance characteristics of goats fed diet 4 with 30% inclusion level of xylanase-treated rice husk was significantly (p0.05) higher than other treatment diets. The inclusion of xylanase-treated rice husk up to 30% in goats diet may haveincreased nutrients and dry matter digestion, total volatile fatty acids (TVFA's) and microbial protein production. The study concluded that xylanase-treated rice husk included at 30% in the diets of WAD goats improved feeding values of feed byincreasingthe rumen fermentation of fibrous diets and enhanced the growth performance of WAD goats.